MODIFIKASI SISTEM NITROGEN PADA SAAT START-UP PABRIK AMMONIA 1A MENGGUNAKAN COMPRESSOR NATURAL GAS BOOSTER - Farah Fitri Annisa; Mentari Adinda Fithia; Zainal Arifin; Dedy Irawan; Majus Luther Sirait (JURNAL TEKNIK KIMIA VOKASIONAL (JIMSI), 2021)
Start up is the first step in the operation of the factory. The start-up process at the Ammonia Plant Operations department 1A requires some preparation, namely draining the entire system with nitrogen and the required system line-up. Nitrogen circulation is used for heating up several units, such as reformers and bycatch. Heating up is done so that the temperature of the reformer and bycatch units can be quickly achieved and the process can take place immediately. The description of the heating up process when improvised nitrogen circulation is carried out using a natural gas booster compressor, this process simultaneously goes through the desulfurized unit for heating up. So there is no need to use natural gas for heating up the desulfurization unit and then throwing it away. The responses carried out are data analysis, data collection and data processing. Based on the results of the economic analysis, it can be seen that at start-up by carrying out improvement conditions it will be more efficient because natural gas that is usually wasted is no longer wasted and gains additional profits from the gas, production will be 3 hours faster so that profits increase, and save the amount of process gas and fuel used for the start-up process for 3 hours. And the time needed to return the capital issued is four times the start up.